Metastatic adenocarcinoma of the mandible. (28th November 2016) - McGoldrick, D.M.; Brady, P.; Sleeman, D.
Abstract: A 58‐year‐old gentleman presented to the Oral and Maxillofacial Surgery Department having been referred by his dentist with a non‐healing post‐extraction socket. Examination revealed an intraoral mass and an associated suspected pathological fracture of the right body of the mandible. He had a background of metastatic adenocarcinoma of the sigmoid colon. Subsequent biopsy of the mandibular mass confirmed metastatic spread to the mandible, a rare presentation. The patient was managed conservatively given his extensive co‐morbidities.